Program Penanaman Mangrove Untuk Pemulihan Ekositem Pesisir Rangge Di Pulau Pari, Jakarta - Riyan Ariyansah; Oktarina Heriyani; Rifky Rifky; Mugisidi Mugisidi (Cv. Utility Project Solution, 2023)
Planting mangrove trees on Pari Island, Jakarta, is an effective solution to address coastal ecosystem degradation and loss of biodiversity. This research aims to explain the method of mangrove tree planting involving the participation of local communities and analyze its impact on coastal ecosystems and community well-being. Through problem identification, goal formulation, research design, data collection, data analysis, and interpretation of results, significant scientific findings are obtained. The first scientific finding is an increase in biodiversity after mangrove tree planting. The research shows that planting mangrove trees provides an ideal habitat for various organisms, including fish, mollusks, and birds, thereby increasing the number of species inhabiting the mangrove ecosystem. The second scientific finding is an improvement in water quality around the mangrove planting area. Mangroves have the ability to absorb nutrients and reduce pollution levels in the water. Therefore, after planting, there is a decrease in the levels of pollutants such as heavy metals and nutrients in the surrounding waters. This study also found that mangrove ecosystems play a role in natural disaster mitigation. Planting mangrove trees reduces coastal erosion because the complex and robust root systems of mangroves help maintain soil stability. Comparisons with previous research support these scientific findings, indicating that planting mangrove trees effectively enhances biodiversity, improves water quality, and reduces coastal erosion.